Ab initio study of the magnetic ordering in Si/Mn digital alloys - M. M. Otrokov and Arthur Ernst and V. V. Tugushev and Sergey Ostanin and Pawel Buczek and Leonid M. Sandratskii and G. Fischer and W. Hergert and Ingrid Mertig and V. M. Kuznetsov and E. V. Chulkov (Physical Review B : Condensed Matter and Materials Physics, 2011)
We present a first-principles study of the electronic structure and exchange interactions in Si/Mn digital magnetic alloy (DMA) consisting of Mn monolayers embedded in a Si matrix stacking along [001] direction. The main focus of our study is on the dependence of magnetic properties on the morphology of the Mn monolayer. Three different structural models for the Mn monolayer are considered: manganese in substitutional (i), interstitial (ii), and both interstitial and substitutional (iii) positions. The atomic positions in Si/Mn DMA are determined by means of the VASP code and then serve as input for multiple-scattering calculations of the electronic and magnetic structure. The magnetic force theorem is used to evaluate the exchange coupling parameters. A Heisenberg model based on those parameters is used to estimate magnon frequencies and magnetic phase-transition temperatures for different anisotropies. The magnetic properties of Si/Mn DMA are found to be strongly dependent on the underlying crystalline structure. © 2011 American Physical Society.